Biodiversity conservation, law + livelihoods bridging the north-south divide - Jeffery, Michael I. 1942-; Firestone, Jeremy M.; Bubna-Litic, Karen 1956- (IUCN Academy of Environmental Law research studies, 2008)
The IUCN Academy of Environmental Law Research Studies' third colloquium of 2005 brought together more than 130 experts from 27 nations on nearly every continent. This book brings together a number of the papers presented there and offers a global perspective on biodiversity conservation and the maintenance of sustainable cultures. It addresses issues from international, regional, and country-specific perspectives. The book is organized thematically to present a broad spectrum of issues, including the history and major governance structures in this area; the needs, problems, and prerequisites for biodiversity; area-based, species-based, and ecosystem-based conservation measures; the use of components of biodiversity and the processes affecting it; biosecurity; and access to and sharing of benefits from components of biodiversity and their economic value